Review on the Barriers Of Mathematics - Dev, Sandeep Kaur (IJRDO -JOURNAL OF MATHEMATICS, 2015)
nd Year 8-10 secondary school students. The negative dimensions of mathematics anxiety, self-esteem, and proactive coping correlated negatively with mathematics achievement and were both poor predictors of and barriers to mathematics achievement. In addition, females scored significantly higher on negative self-esteem and forward stress variables than males. Overall, the findings have practical significance indicating psychological areas where attention, counseling efforts and educational interventions need to be directed to help the at-risk and weak students .